The Impact Of Theodor Drayzer's Work On American Literature (Eurasian Research Bulletin, 2022)
This article is devoted to the works of the American writer and public figure, talented journalist Theodore Dreiser. The article discusses his contribution to American literature and the depiction of social problems in his works, the diversity of the main characters of his works.